2021
DOI: 10.1002/ece3.8214
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity buffers the effects of a pulse perturbation on the dynamics of tritrophic food webs

Abstract: Biodiversity decline causes a loss of functional diversity, which threatens ecosystems through a dangerous feedback loop: This loss may hamper ecosystems’ ability to buffer environmental changes, leading to further biodiversity losses. In this context, the increasing frequency of human‐induced excessive loading of nutrients causes major problems in aquatic systems. Previous studies investigating how functional diversity influences the response of food webs to disturbances have mainly considered systems with at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 74 publications
(130 reference statements)
3
9
0
Order By: Relevance
“…Therefore, the model is effectively four-dimensional, corresponding to three trophic levels and the nutrient pool. The comparison between a food chain and food webs with higher levels of functional diversity is nonetheless meaningful: when the trait values of all species at the same trophic level are identical, the system’s equations can be rewritten by introducing new state variables B, I , and T such that B = B u + B d , I = I us + I un + I ds + I dn , and T = T s + T n , which allow for the recovery of the equations for a four-dimensional food chain, as detailed in previous studies using the same model [Ceulemans et al, 2019, Wojcik et al, 2021] and justified by [Moisset de Espanés et al, 2021]. In addition, all calculations were performed at the trophic level (rather than the species level) to unify the comparison.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the model is effectively four-dimensional, corresponding to three trophic levels and the nutrient pool. The comparison between a food chain and food webs with higher levels of functional diversity is nonetheless meaningful: when the trait values of all species at the same trophic level are identical, the system’s equations can be rewritten by introducing new state variables B, I , and T such that B = B u + B d , I = I us + I un + I ds + I dn , and T = T s + T n , which allow for the recovery of the equations for a four-dimensional food chain, as detailed in previous studies using the same model [Ceulemans et al, 2019, Wojcik et al, 2021] and justified by [Moisset de Espanés et al, 2021]. In addition, all calculations were performed at the trophic level (rather than the species level) to unify the comparison.…”
Section: Methodsmentioning
confidence: 99%
“…This so-called functional diversity may be quantified as the difference in functional traits (such as edibility or prey selectivity) between species at the same trophic level. A few theoretical studies have demonstrated that the ability of predator and prey species to adapt their respective levels of offence and defence greatly improved resistance to perturbations [Raatz et al, 2019, Wojcik et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations